Junie B. Jones and a little monkey business - Park, Barbara (Park, Barbara. Junie B. Jones series, 1993)
Through a misunderstanding, Junie B. thinks that her new baby brother is really a baby monkey, and her report of this news creates excitement and trouble in her kindergarten class.